The in-use stability of the rituximab biosimilar Rixathon®/Riximyo® upon preparation for intravenous infusion. (March 2019) - Lamanna, William C; Heller, Katharina; Schneider, Daniel; Guerrasio, Raffaele; Hampl, Veronika; Fritsch, Cornelius; Schiestl, Martin
Purpose: The purpose of this study was to evaluate the in-use physicochemical and biological stability of the Sandoz rituximab biosimilar, marketed under the trade names Rixathon® and Riximyo® in the European Union, upon preparation for intravenous infusion. Methods: Three batches of Rixathon®/Riximyo® in the final month of their 36 month shelf life were exposed to room temperature and light for 14 days to recapitulate a major temperature excursion. Samples were diluted to the lowest allowable concentration of 1 mg/mL in 0.9% NaCl solution in either polypropylene or polyethylene infusion bags and stored for 14 or 30 days at 5 ± 3℃ followed by an additional 24 h at room temperature to simulate product handling. Samples stored in infusion bags were analyzed using SEC, CEX, non-reducing CE-SDS, peptide mapping and CDC to assess physicochemical and biological stability. Results: Analysis of Rixathon®/Riximyo® diluted to the lowest allowable concentration in 0.9% sodium chloride in either polypropylene or polyethylene infusion bags revealed no change in molecular weight variants, charge variants, deamidation, oxidation, overall composition or potency over a 31-day period. Conclusion: Physicochemical and biological analyses demonstrate that Rixathon®/Riximyo® stability is not impacted by dilution and formulation conditions required for intravenous infusion, even under worst case conditions with regard to product shelf life, temperature excursion, light exposure, dilution factor and infusion bag storage time over a 31-day period.